Main modern problems of doping in sport - Rudenko, V.P. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : to identify and substantiate medico-biological, psychological and social problems of doping in sport. Material: Theoretical study is based on analysis of more than 50 scientific and methodical literatures. Results : it was shown that doping is one of the serious problems of modern sport and society in general. Defines important questions regarding anti-doping rules and the anti-doping control in sport. Installed the use of performance enhancing drugs in professional sports for children and youth. Given the promising solutions to the problems of doping in Ukraine. Conclusions: Among the problems of modern sport is becoming increasingly important issue of doping. It is an extremely complex because it involves the interrelated medical, legal, political, moral, organizational, social and pedagogical aspects. Socio-pedagogical factors of anti-doping policy in sports scientists comprehensively still not addressed. Certain aspects of anti-doping policy presented in scientific papers, which can be divided into two groups. The first group of papers is devoted to doping in sport as a social event. The second group of papers devoted to the problems of doping control. Today there is a need and objective preconditions for the development and adoption of a General concept, which would be generalized numerical amount of data received and served as a basis for developing an effective anti-doping control at the expense of improvement of legislative and normative-legal base and infrastructure of the anti-doping policy in Ukraine, which should be brought in line with modern international standards.